Comparing IMF-sensitive indices of intermediate-mass quiescent galaxies in various environments. Issue 3 (18th April 2019) - Eftekhari, Elham; Mosleh, Moein; Vazdekis, Alexandre; Tavasoli, Saeed
ABSTRACT: Using samples drawn from the Sloan Digital Sky Survey, we study for the first time the relation between large-scale environments (clusters, groups, and voids) and the stellar initial mass function (IMF). We perform an observational approach based on the comparison of IMF-sensitive indices of quiescent galaxies with similar mass in varying environments. These galaxies are selected within a narrow redshift interval (0.020 < z < 0.055) and spanning a range in velocity dispersion from 100 to 200 km s −1 . The results of this paper are based upon analysis of composite spectra created by stacking the spectra of galaxies, binned by their velocity dispersion and redshift. The trends of spectral indices as measured from the stacked spectra, with respect to velocity dispersion, are compared in different environments. We find a lack of dependence of the IMF on the environment for intermediate-mass galaxy regime. We verify this finding by providing a more quantitative measurement of the IMF variations among galactic environments using MILES stellar population models with a precision of ΔΓb ∼ 0.2.